The Rheumatoid Arthritis-Associated Citrullinome. Issue 6 (21st June 2018) - Tilvawala, Ronak; Nguyen, Son Hong; Maurais, Aaron J.; Nemmara, Venkatesh V.; Nagar, Mitesh; Salinger, Ari J.; Nagpal, Sunil; Weerapana, Eranthie; Thompson, Paul R.
Summary: Increased protein citrullination is linked to various diseases including rheumatoid arthritis (RA), lupus, and cancer. Citrullinated autoantigens, a hallmark of RA, are recognized by anti-citrullinated protein antibodies (ACPAs) which are used to diagnose RA. ACPA-recognizing citrullinated enolase, vimentin, keratin, and filaggrin are also pathogenic. Here, we used a chemoproteomic approach to define the RA-associated citrullinome. The identified proteins include numerous serine protease inhibitors (Serpins), proteases and metabolic enzymes. We demonstrate that citrullination of antiplasmin, antithrombin, t-PAI, and C1 inhibitor (P1-Arg-containing Serpins) abolishes their ability to inhibit their cognate proteases. Citrullination of nicotinamide N-methyl transferase (NNMT) also abolished its methyltransferase activity. Overall, these data advance our understanding of the roles of citrullination in RA and suggest that extracellular protein arginine deiminase (PAD) activity can modulate protease activity with consequent effects on Serpin-regulated pathways. Moreover, our data suggest that inhibition of extracellular PAD activity will be therapeutically relevant. Graphical Abstract: Highlights: Identified citrullinated proteins in RA serum, synovial fluid, and synovial tissue Citrullination of NNMT abolishes its methyltransferase activity Serpin citrullination abolishes their ability to inhibit their cognate proteases Serpin citrullination modulates Serpin-regulated pathways Abstract : Tilvawala et al. demonstrated that protein citrullination is elevated in RA and defined the RA-associated citrullinome. Tilvawala et al. further discovered that Serpin citrullination abolishes their ability to inhibit their cognate proteases. These studies open a new avenue to understand the links between protein citrullination and numerous diseases.